Pengaruh penanaman modal dalam Negeri, penanaman modal asing dan ekspor terhadap PDRB Provinsi Jambi Periode 2000- 2016 - Tarmizi Tarmizi; Siti Hodijah; Rosmeli Rosmeli (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to analyze the development of GRDP, domestic investment, foreign investment, and exports in Jambi Province for the period 2000-2016, as well as to study the effect of domestic investment, foreign investment, and exports on the growth of GRDP of Jambi Province in the period 2000-2016. 2016. This research uses descriptive and quantitative analysis methods. The descriptive analysis method is used to analyze the development of each research variable, namely domestic investment, foreign investment, and exports. Quantitative analysis methods are used to analyze the effect of domestic investment, foreign investment, and exports on the growth of GRDP in Jambi province for the period 2000-2016. Based on the study results, the Jambi Province GRDP growth for the 2000-2016 period was 7.21 percent, domestic investment growth was 11.64 percent, foreign investment was 18.69 percent, and export development was 17.83 percent. And during the period 2000-2016, domestic investment, foreign investment, and exports had a significant effect on GRDP growth in Jambi Province. Keywords: Domestic investment, Foreign investment, Exports, PDRB Growth